Quality of Life and Exercise Adherence in Individuals with Chronic Inflammatory Skin Diseases: A Narrative Review - Zinko, Oksana; Buczyńska-Dymicka, Karolina; Bajek, Martyna; Puchalski, Konrad; Polakowska, Izabela; Urban-Michalak, Karolina; Bigdoń, Anna; Pietrzak-Chmiel, Martyna Maria; Malinowski, Kamil; Gosztyła, Dominika (Quality in Sport, 2026)
Background. Chronic inflammatory skin diseases (CISDs) such as atopic dermatitis, psoriasis, hidradenitis suppurativa and chronic spontaneous urticaria significantly impair health-related quality of life (HRQoL). Symptoms (itch, pain), heat/sweat sensitivity, and psychosocial burden (stigma, anxiety) may also reduce physical activity participation and undermine long-term exercise adherence, yet the evidence remains fragmented across conditions. Aim. To synthesize current evidence on the relationship between HRQoL impairment and exercise participation/adherence in individuals with CISDs and to identify recurring barriers and facilitators relevant for clinical and exercise counseling. Material and methods. A narrative review was conducted using targeted searches of PubMed and Google Scholar and reference-list screening. Search terms combined CISD diagnoses (atopic dermatitis, psoriasis, hidradenitis suppurativa, chronic urticaria) with HRQoL and physical activity constructs (DLQI, Skindex, physical activity, exercise, adherence, barriers, facilitators, lifestyle intervention). English-language publications were prioritized; selected non-Russian sources in other languages were considered when relevant. Conclusions. Exercise adherence in CISDs is shaped by interacting symptom, psychosocial, and environmental factors closely aligned with HRQoL domains. Multi-component, individualized strategies combining optimized disease control with barrier-aware exercise counseling are most likely to support sustainable physical activity.